Answer :

Let’s express the variable in terms of another variable.

2(x - y) = 3 ………[1]


2x - 2y = 3


2x = 3 + 2y


………[3]


and,


5x + 8y = 14 ………[2]


5x = 14 – 8y


………[4]


on comparing eq. [3] and eq. [4]


we get,



15 + 10y = 28 – 16y


26y = 13


………[5]


from eq. [3]





………[6]


by eq. [5] and [6]


x = 2,


by using the result in eq. [1] and eq. [2]


2(x - y) = 3


L.H.S




= 3 = R.H.S


similarly,


by eq. [2]


5x + 8y = 14


L.H.S



= 10 + 4


= 14 = R.H.S


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Equations of MotionEquations of MotionEquations of Motion41 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Let us solve the West Bengal Mathematics

By comparing the West Bengal Mathematics

Let us solve the West Bengal Mathematics

Let us solve the West Bengal Mathematics

Let us solve the West Bengal Mathematics

By comparing the West Bengal Mathematics

By comparing the West Bengal Mathematics

By comparing the West Bengal Mathematics

Let us solve the West Bengal Mathematics

Let us solve the West Bengal Mathematics